The Implementation of Synchronous and Asynchronous Learning in English As Foreign Language Setting - Sulha, Alice Hijrah; Famela, Anelsa Kintan; Harahap, Anggi Tri Annisa (ETDC: Indonesian Journal of Research and Educational Review, 2021)
The aims of this paper are to provide an understanding to synchronous and asynchronous learning and its implementation in EFL setting. This can be seen from the definition of synchronous and asynchronous learning until the implementation of synchronous and asynchronous learning in EFL setting. This writing is made in the form of a study of documents and literatures whose understanding of knowledge is used as an analysis. The synchronous and asynchronous learning can help the students to enhance language skills. In view of this, the teachers, instructors, and administrators have to consider the students’ need and background knowledge in implementing synchronous and asynchronous learning in teaching EFL.